Anaerobic granular reactors for the treatment of dairy wastewater: A review - Karadag, Dogan; Koroglu, Oguz Emre; Ozkaya, Bestami; Cakmakci, Mehmet; Heaven, Sonia; Banks, Charles; Serna-Maza, Alba (WILEY, 2015)
Considerable research has been conducted on the treatment of dairy wastewater by anaerobic granular reactors. Upflow anaerobic sludge blanket (UASB) reactors, anaerobic sequencing batch reactors (ASBR) and static granular bed reactors (SGBR) are the conventional granular reactor types most commonly applied in dairy wastewater treatment. Hybrid systems have also been developed to increase treatment efficiency and overcome the operational problems associated with the treatment of this substrate. Effects of parameters including temperature, organic loading and operating protocols on the performance of granular reactors are summarised. Individual and hybrid granular reactors are evaluated based on organic matter removal and methane production capacity.
Keywords: Dairy wastewater; Granular reactor; Methane; Organic loading; SLUDGE BLANKET REACTOR; CHAIN FATTY-ACIDS; UASB REACTOR; CHEESE-WHEY; BIOGAS PRODUCTION; HIGH-STRENGTH; BED REACTOR; COMPARATIVE PERFORMANCE; LOW-TEMPERATURE; DIGESTION; Food Science & Technology